The Chessmen of Mars - Burroughs, Edgar Rice, 1875-1950 (Salt Lake City, UT : Project Gutenberg, 1998)
"The Chessmen of Mars" by Edgar Rice Burroughs is a science fantasy novel published in 1922. When Tara, princess of Helium and daughter of John Carter, crashes her flier in a storm, she finds herself captured by the horrific Kaldanes$1 (Blarge heads with crab-like legs who ride headless human bodies. Prince Gahan of Gathol sets out to rescue her, but conceals his identity as a humble mercenary. Together they must survive the deadly city of Manator, where captives fight to the death as living pieces in a giant chess game. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Chessmen_of_Mars
Release date is 1998-01-01
Produced by Judy Boss
Keywords: Science fiction; Mars (Planet) -- Fiction